2021
DOI: 10.3390/microorganisms9030579
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Estimation Capability of Response Surface Methodology and Artificial Neural Network for the Optimization of Bacteriocin-Like Inhibitory Substances Production by Lactococcus lactis Gh1

Abstract: Bacteriocin-like inhibitory substances (BLIS) produced by Lactococcus lactis Gh1 had shown antimicrobial activity against Listeria monocytogenes ATCC 15313. Brain Heart Infusion (BHI) broth is used for the cultivation and enumeration of lactic acid bacteria, but there is a need to improve the current medium composition for enhancement of BLIS production, and one of the approaches is to model the optimization process and identify the most appropriate medium formulation. Response surface methodology (RSM) and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The cell viability was evaluated according to method as that defined in Jawan et al [25]. Briefly, cell viability was examined using spread plate method and reported as colony forming units (CFU/mL).…”
Section: Methodsmentioning
confidence: 99%
“…The cell viability was evaluated according to method as that defined in Jawan et al [25]. Briefly, cell viability was examined using spread plate method and reported as colony forming units (CFU/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, AMPs released by secretome proteins act as host defences, where many of them have been isolated from living entities, such as bacteria, animals, plants, and fungi (Zainal Baharin et al, 2021;Kumar, Kizhakkedathu & Straus, 2018). In previous studies, secretome proteins from Paenibacillus polymyxa Kp10 (Kp10) and Lactococcus lactis Gh1 (Gh1) were shown to display antimicrobial activity and could potentially replace antibiotics (Zainal Baharin et al, 2022;Mokhtar et al, 2020;Jawan et al, 2021). A recent study showed that Gh1 exhibited antimicrobial activity against pathogenic Staphylococcus aureus, Listeria monocytogenes, Salmonella and Bacillus cereus species (Jawan et al, 2020), while Kp10 was shown to demonstrate antimicrobial activity against Escherichia coli (Mokhtar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that different Bacillus licheniformis strains require specific media to achieve maximum conidial production; thus, we optimized a fermentation medium formulation suitable for Bacillus licheniformis by means of mathematical modeling. One-factor-at-a-time (OFAT) experiments represent a classical and effective screening method, which allows for the initial screening of fermentation medium formulations and the determination of the corresponding concentration range (Jawan et al, 2021). Response surface methodology (RSM) is a relatively new statistical method that allows the response value of a system to be visualized as a function of one or more factors and the test results to be represented graphically (Zhilong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%